Particularities of clinical manifestations of infectious inflammatory process in women with uncomplicated and complicated pregnancy course - V V Skryabina (IP Berlin A.V., 2013)
The peculiarities of the clinical symptoms of the inflammatory process in women with physiological and complicated course of pregnancy. It is shown that in the physiological course of pregnancy act of infectious agents and endogenous intoxication leads to the anatomical lesions only the placenta, and when complicated course to the defeat of the placenta, the formation of functional disorders (threat of termination of pregnancy, hypoxia and delays in the development of the newborn) and organic changes (congenital malformations and fetopatiy) in the child.